Treatment Outcome of Tuberculosis in HIV Seropositive Patients: An Experience of Southeast Region of Ahmedabad - Tripathi, Sanjay B; Kapadia, Vishakha K (National Journal of Community Medicine, 2015)
Objectives: To evaluate the clinical profile and the factors influencing treatment outcome of TB patients co-infected with HIV attending DOT centers of Southeast area of Ahmedabad, Gujarat Methodology: A Prospective observation study was conducted to assess the treatment outcome of TB in TB-HIV co-infected patients on DOTs conducted at L.G. Hospital and tuberculosis units (TUs) of south and east region of Ahmedabad. TB patients started DOTS were registered and were followed till treatment outcome was declared. Results: The treatment success rate was found to be 84.17% (101 of 120 patients). Treatment success rate of Tuberculosis among HIV se- ropositive patients was significantly associated with WHO clinical and Functional staging (p value <0.001), alcoholism (p value <0.001) and drug intolerance (p value <0.001).No significant association was found with concurrent Anti Retro Viral Therapy and socio economic classes. Conclusion: The DOTS was found to be as effective in HIV seroposi- tive, so it should be strengthened, in order to control the HIV-TB epi- demic.